Pro-Environmental Communication and Behavior in Sustainable Use of Environmental Resources: A Study in Kalpitiya Fisheries Inspector Division, Sri Lanka - M. D. K. L. Gunathilaka; V. P. I. S. Wijeratne (International Journal of Environment, Engineering and Education, 2022)
Human behavior has a multi-dimensional view of resource utilization; thus, vital to examine the behavior of groups in environmental resource utilization. The group was fishing communities in Kalpitiya Fisheries Inspector Division (KFID). Data was collected through various methods subjected to thematic content-based analysis and statistical analysis. The primary source of income is a fishery where marine fishery and brackish water fishery, along with aquaculture, were the sub-categories. Sixteen percent were engaged in both marine and brackish water fishery. A total of 18116 individuals were marginalized in the area. Un-sustainable resource utilization has decreased the area's existing resources, particularly for Internally Displaced Persons (IDPs). Their behavior has created specific environmental problems in Wannimundalama and Manadalakuda. Though education level was not satisfactory (96%), the statistical analysis showed dis-concordant status; neither education nor the source of income affects their poor behavior in resource utilization. Comparing two fishing harbors illustrated that the cultural aspect also affects the behavior. The perception of environmental protection is also poor, IDPs. Gender vice behavior reflected that females are more willing to protect and restore the environment than males. Findings illustrated that the dimensions and categories of the system directly do not decide the behavior of groups in environment resource utilization. Environmental communication is essential and positively impacts human behavior in environmental resource utilization. The study recommends investigating the factors constraining sustainable resource utilization behavior in KFID, emphasizing the necessity of environmental communication.